CUSTOMER SATISFACTION TOWARDS E-BANKING SERVICES WITH REFERENCE TO ICICI BANK - KANAGARAJU, Dr.P.; BALAMURUGAN, G. (The journal of contemporary issues in business and government, 2021)
Indian banks are trying to make your life easier. Not just bill payment, you can make investments, shop or buy tickets and plan a holiday at your fingertips. In fact, sources from ICICI Bank tell us, "Our Internet banking base has been growing at an exponential pace over the last few years. Currently around 78 percent of the bank's customer base is registered for Internet banking." To get started, all you need is a computer with a modem or other dial-up device, a checking account with a bank that offers online service and the patience to complete about a one-page application- which can usually be done online.